A descriptive analysis of anglicism in Ecuadorean magazines - Mendoza Caguana, Alba Patricia (2012)
The following research is about “A Descriptive Analysis of Anglicisms in Ecuadorian Magazines” which has been considered with the purpose of researching on the linguistic phenomenon of anglicisms used in Ecuadorian Magazines. In order to carry out this research, six Ecuadorian Magazines were used. For this reason, I selected two cultural magazines from Paute, with the title “PAU-TI” first and second edition; two scholarly magazines from Cuenca city, with the themes “Gestión Economía y Sociedad” and “PC Word”; and two of general interest magazines, which are well known in the country: “Vistazo” and “Hogar”. For this research to be successful, I applied qualitative and quantitative methods which helped me to analyze in a descriptive and in a comparative form the use of anglicisms in our vocabulary through magazines. As a conclusion of the analysis, it was noticed that in scholarly and general interest magazines there were more anglicisms than in cultural ones since in cultural magazines, the writers try to keep in the culture and language of their provinces; so, they are more careful in the use of the correct words. On the other hand, the high incidence of anglicisms in scholarly and general interest magazines mainly occurs because of the use of new technological terms that have been introduced in our language.